The Influence Of Product Quality, Brand Image, And Trust On Consumer Purchasing Decisions In Parfume Batam City - Atika Yusniari; Nora Pitri Nainggolan (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
Nowadays, appearance is the focus of everyone's attention, from make-up, clothing, to grooming. The company has introduced various quality products and brands that consumers can easily recognize. Consumers can decide whether to trust and buy the product based on its quality and brand. The aim of this research is to analyze product quality, brand image and trust in perfume purchasing decisions at In Parfume, Batam City. This research uses descriptive quantitative research methods. The population of this study is unknown and the sample in this study consisted of 100 respondents. The sampling technique uses the lemeshow formula. Primary data was obtained by distributing questionnaires to respondents using Likert scale measurements. This data processing uses SPSS version 25 analysis techniques. Based on the results of this research, product quality, brand image and trust partially and simultaneously influence consumer purchasing decisions in Batam City.